Method for preparing high-purity ammonium metavanadate by purifying ammonium polyvanadate

In the preparation process of high-purity ammonium metavanadate, the flocculation and precipitation technology that controls pH value is used to solve the problems of complex processes, high cost and high energy consumption in the existing technology, and the preparation of high-purity ammonium metavanadate and efficient recovery of vanadium resources are achieved.

CN119797423APending Publication Date: 2025-04-11ZAOYANG DALI ENERGY STORAGE TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510035537.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has problems such as complex process flow, high purification cost, high wastewater and high energy consumption in the preparation process of high purity ammonium metavanadate, making it difficult to simplify, diversify and clean the vanadium recycling and purification process.

Method used

After dissolving ammonium polyvanadate, it is subjected to a conversion reaction with ammonium ammonia water, and then adding silicone remover and iron remover at a controlled pH value for flocculation and precipitation, and finally cooling and crystallization is carried out to obtain high-purity ammonium metavanadate.

Benefits of technology

The preparation of ammonium metavanadate with a high purity of more than 99.5% was achieved, the process flow was simplified, energy consumption and wastewater generation were reduced, vanadium recovery was improved, and it met the requirements of industrial clean production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797423A_ABST
    Figure CN119797423A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-purity ammonium metavanadate by purifying ammonium polyvanadate, according to the method, the ammonium polyvanadate with various impurities is used as a raw material, the pH value of a solution is controlled step by step, and main impurities such as Si and Fe in the solution are sequentially removed by using a proper reagent, so that high-purity vanadium with the purity of 99.5% or above can be obtained, the content of impurity elements is low, and the requirements of electrolyte, electrolyte and the like can be met. In the aspect of aeronautical manufacturing, the purity requirement of vanadium products is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ammonium metavanadate preparation, in particular to a method for purifying ammonium polyvanadate to prepare high-purity ammonium metavanadate. Background Art

[0002] High-purity ammonium metavanadate (NH4VO3) is an important chemical raw material, widely used in the production of high-purity vanadium oxides, catalysts, vanadium electrolytes, etc. With the advancement of science and technology and the improvement of environmental protection requirements, the demand for high-purity ammonium metavanadate has steadily increased, especially in vanadium energy storage projects. The development of all-vanadium flow batteries has brought new market opportunities for high-purity ammonium metavanadate.

[0003] In the background technology of preparing high-purity ammonium metavanadate, the traditional vanadium extraction process has some problems, such as high energy consumption, harsh production environment, large ammonia absorption loss, etc. In order to solve these problems, some new technologies have been developed to improve production efficiency and product quality while reducing costs and environmental impact.

[0004] In addition, some studies have explored methods for recovering vanadium from vanadium-containing waste catalysts. These methods can not only provide high-purity ammonium metavanadate, but also achieve harmless treatment of waste catalysts and recycling of resources, which meets the requirements of environmental protection and sustainable development.

[0005] In practical applications, the production technology of high-purity ammonium metavanadate has reached the domestic leading level, and the product quality can meet the needs of the high-end market. With the gradual commercialization of vanadium energy storage projects, the market demand for high-purity ammonium metavanadate is expected to grow further, and the market development prospects are very optimistic.

[0006] Chinese patent document CN107298461A discloses a method for purifying ammonium metavanadate and a method for high-purity ammonium metavanadate. The method firstly carries out vanadium adsorption and analysis on a vanadium-containing solution by using an alkaline anion exchange resin, and then vanadium adsorption and analysis are carried out on an acidic cation exchange resin, and ammonium metavanadate is obtained and then recrystallized, washed, and dried to finally obtain high-purity ammonium metavanadate. Although this method can obtain high-purity ammonium metavanadate, it is necessary to carry out two resin exchange adsorptions, the process flow is complicated, the purification cost is high, and there is much process wastewater, which does not meet the actual production conditions.

[0007] Chinese patent document CN107285381A discloses an ammonium metavanadate and a preparation method thereof, wherein the preparation method comprises dissolving ammonium polyvanadate in a strong alkaline solution, adding ammonium chloride, filtering to obtain a white solid, washing, drying, recrystallizing, washing, and drying to obtain ammonium metavanadate. This method requires washing and drying the product twice while obtaining high-purity ammonium metavanadate, which not only consumes a lot of energy, but also generates a large amount of ammonia nitrogen wastewater that needs to be treated, and the environmental protection treatment cost is relatively high.

[0008] In recent years, the recycling and purification technology of vanadium resources and environmentally friendly purification processes have received more and more attention. The method of preparing high-purity ammonium metavanadate from ammonium polyvanadate needs further research to achieve the goal of simplifying, diversifying and cleaning the vanadium recycling and purification process. Summary of the invention

[0009] The present invention aims to provide a method for purifying ammonium polyvanadate to prepare high-purity ammonium metavanadate, which is used to solve at least one of the many defects of the prior art, such as complex process flow, high purification cost, large amount of wastewater, high energy consumption, etc., and promote the industrial process of vanadium recovery and purification technology.

[0010] In view of this, the scheme of the present invention is:

[0011] The first aspect of the present invention is to provide a method for purifying ammonium polyvanadate to prepare high-purity ammonium metavanadate, the steps comprising:

[0012] S1. After dissolving the ammonium polyvanadate, adding ammonia water to carry out the ammonium conversion reaction;

[0013] S2. The pH value of the solution after ammonium conversion is adjusted to 8-8.5, and then a desiliconizing agent is added, and the solution is filtered after sufficient desiliconization;

[0014] S3. The pH value of the solution obtained in step S2 was adjusted to 7-7.6, and then an iron removal agent and sodium carboxymethyl starch solution were added, and the mixture was fully flocculated and filtered;

[0015] S4. The pH value of the solution obtained in step S2 is adjusted to 8-9, then cooled and crystallized, and filtered to obtain high-purity ammonium metavanadate;

[0016] The silicon removal agent is polyferric sulfate and / or calcium oxide;

[0017] The iron remover is polyaluminium chloride and / or polyaluminium sulfate.

[0018] Further, the content of V2O5 in the ammonium polyvanadate is 85-90%, for example, it can be 85.0%, 85.2%, 85.8%, 86.0%, 86.3%, 87.0%, 87.5%, 88.0%, 88.6% or 90.0%, etc., but it is not limited to the listed values, and other unlisted values ​​in this range are also applicable. Impurities include by mass percentage: Ca 0.1-0.3%, Al 0.1-0.3%, Si 0.25-0.4%, Fe 0.3-0.5%, and the sum of Na and K is 1.1-2.0%. The source of the ammonium polyvanadate can be a primary product prepared by roasting, reacting, vanadium precipitation, etc. of raw materials such as vanadium slag and stone coal.

[0019] It should be noted that the content of V2O5 in the ammonium polyvanadate used in the method for preparing high-purity ammonium metavanadate of the present invention is essentially not limited, and the same is applicable to V2O5 with a higher content when similar impurities are present; for V2O5 with a lower content, it is only necessary to adaptively adjust the amount of reagents when a higher content of impurities is present.

[0020] Furthermore, in step S1, ammonia water is added during the transammonium reaction process to a pH of 7-9, for example, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8 or 9.0; the transammonium reaction time is 0.5-1h, for example, 0.50h, 0.55h, 0.60h, 0.65h, 0.70h, 0.75h, 0.80h, 0.85h, 0.90h, 0.95h or 1.00h, etc.

[0021] Further, in step S2, the pH of the desiliconization reaction can be 8.00, 8.05, 8.10, 8.15, 8.20, 8.25, 8.30, 8.35, 8.40, 8.45 or 8.50, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable. The principle of polyferric sulfate and calcium oxide desiliconization is that the iron hydroxide or calcium hydroxide colloid generated by its hydrolysis carries a positive charge, and the colloidal silica in the solution carries a negative charge, so flocculation and precipitation occur after charge neutralization to achieve the purpose of desiliconization. The generation of this colloid needs to be within a suitable pH range of pH=8-9.5. In the range of pH=7-9, as the pH increases, the removal effect of Si is better, so Si needs to be removed at a higher pH first. However, at this pH, the added Fe or Ca salt desiliconizer is excessive and needs to be removed by the subsequent iron removal agent. The removal of Fe or Ca needs to be carried out under slightly lower pH conditions. Therefore, the subsequent iron removal process needs to adjust the pH back to the range of pH = 7-7.6.

[0022] Furthermore, the concentration of the desiliconizer is 10-15wt%, for example, it can be 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5% or 15.0%, etc.; the molar ratio of the added amount of the desiliconizer to the silicon in the solution after ammonium conversion is (2-4):1, for example, it can be 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4.0:1, etc.

[0023] Further, in step S2, the desiliconization reaction temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, etc.; the reaction time is 0.5-1h, which can be 0.50h, 0.55h, 0.60h, 0.65h, 0.70h, 0.75h, 0.80h, 0.85h, 0.90h, 0.95h or 1.00h, etc.

[0024] Furthermore, in step S3, the concentration of the deironing agent is 15-20wt%, which can be 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5% or 20.0%, etc.; the molar ratio of the added amount of the deironing agent to the iron in the desiliconizing liquid is (4-6):1.

[0025] Further, in step S3, the iron removal reaction temperature is 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, etc.; the reaction time is 0.5-1h, for example, 0.50h, 0.55h, 0.60h, 0.65h, 0.70h, 0.75h, 0.80h, 0.85h, 0.90h, 0.95h or 1.00h, etc. The principle of removing iron by polyaluminum chloride and / or polyaluminum sulfate is to utilize the strong adsorption characteristics of aluminum hydroxide colloid, and the Fe in the solution is adsorbed and precipitated by the participating colloidal ions, and the aluminum hydroxide colloid needs to be in the range of pH=7-7.6, because Al is an amphoteric metal, which will dissolve under acidic or strongly alkaline conditions, and cannot form a colloid with strong adsorption characteristics, so as to achieve the purpose of impurity removal, so it needs to be in the appropriate pH range. Si and Fe need to be removed within the range of pH = 8-9.5 and pH = 7-7.6, respectively. If Fe is removed at low pH first and Si is removed at high pH, ​​the Fe impurity in the subsequent Si removal solution will exceed the standard, making it impossible to prepare high-purity ammonium metavanadate.

[0026] Further, in step S3, the concentration of sodium carboxymethyl starch is 1-2g / L, for example, 1g / L, 1.1g / L, 1.3g / L, 1.5g / L, 1.6g / L, 1.8g / L or 2.0g / L, etc.; the ratio of the amount of sodium carboxymethyl starch added to the solution obtained in step S2 is 2-5mL:1L, for example, 2.0mL / L, 2.5mL / L, 3.0mL / L, 3.5mL / L, 4.0mL / L, 5.0mL / L. Sodium carboxymethyl starch is used as an organic polymer flocculant in combination with an inorganic polymer flocculant, polyaluminum sulfate or polyaluminum chloride, to improve the flocculation effect of colloidal ions in the solution, and utilizes the linkage and bridging effect between macromolecules to improve the removal effect of macromolecular ions such as Si and Al, and has a removal effect on Na and K ions, thereby improving the purity of vanadium products.

[0027] Further, in step S4, seed crystals are added during the crystallization of ammonium metavanadate, and the addition amount is 1-1.5 g / L, for example, 1 g / L, 1.1 g / L, 1.3 g / L, 1.5 g / L, etc.; the crystallization endpoint temperature is 30-50°C, for example, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, and the crystallization time is 4-6h, for example, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, etc.

[0028] Furthermore, in step S4, the filtered mother liquor is used to dissolve ammonium polyvanadate in step S1.

[0029] Preferably, the liquid-to-solid ratio of the filtered mother liquor to ammonium polyvanadate is (15-20):1, and the temperature of the dissolution process is 70-90°C.

[0030] Compared with the prior art, the beneficial effects of the present invention are at least:

[0031] The purification preparation method of the present invention is based on ammonium polyvanadate with various impurities as raw material. By controlling the pH value of the solution in steps and using appropriate reagents to sequentially remove major impurities such as Si and Fe in the solution, high-purity vanadium with a purity of more than 99.5% can be obtained. The content of impurity elements is small and the purity requirements of vanadium products used in electrolytes and aviation manufacturing can be met.

[0032] The purification preparation method of the present invention has easy-to-obtain raw materials, a short reaction process, low energy consumption loss, a high vanadium recovery rate, and medium recycling, which is more beneficial to environmental protection, conforms to industrial clean production, and promotes the industrial process of vanadium recovery and purification technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1The present invention provides a flow chart of a method for purifying high-purity ammonium metavanadate from ammonium polyvanadate. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described and verified in conjunction with the preferred embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In a specific embodiment, a method for purifying high-purity ammonium metavanadate from ammonium polyvanadate is provided, and its flow diagram is as follows: Figure 1 As shown, the method comprises the following steps:

[0036] S1. After dissolving the ammonium polyvanadate, adding ammonia water to carry out the ammonium conversion reaction;

[0037] S2. The pH value of the solution after ammonium conversion is adjusted to 8-8.5, and then a desiliconizing agent is added, and the solution is filtered after sufficient desiliconization;

[0038] S3. The pH value of the solution obtained in step S2 was adjusted to 7-7.6, and then an iron removal agent and sodium carboxymethyl starch solution were added, and the mixture was fully flocculated and filtered;

[0039] S4. The pH value of the solution obtained in step S2 is adjusted to 8-9, then cooled and crystallized, and filtered to obtain high-purity ammonium metavanadate;

[0040] The silicon removal agent is polyferric sulfate and / or calcium oxide;

[0041] The iron remover is polyaluminium chloride and / or polyaluminium sulfate.

[0042] The following is a preferred implementation example. For those who do not indicate the manufacturer of reagents or instruments in the examples, conventional products can be purchased from the market. For those who do not indicate specific conditions, conventional conditions or manufacturer recommended conditions can be followed. Unless otherwise specified, the data indicating the proportion of components such as "content" and "concentration" are all weight proportions. The ammonium polyvanadate used in the example is a primary product prepared by roasting, reacting, and precipitating vanadium from raw materials such as vanadium slag and stone coal. The content of V2O5 in ammonium polyvanadate is 85-90%, and the content of impurities in ammonium polyvanadate is: Ca 0.1-0.3%, Al 0.1-0.3%, Si 0.25-0.4%, Fe 0.3-0.5%, and the sum of Na and K is 1.1-2.0%.

[0043] Example 1

[0044] Ammonium polyvanadate with a V2O5 content of 90% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.1%, Al 0.1%, Si 0.25%, Fe 0.3%, and Na+K 1.1%.

[0045] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.067g / L, Al 0.067g / L, Si 0.167g / L, Fe 0.2g / L, Na+K 0.733g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 7, and the ammonium transfer reaction time is 0.5h;

[0046] 2) Add 10% polyferric sulfate to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 2:1, the desiliconization pH is 8, the desiliconization temperature is 70°C, the reaction time is 0.5h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.017g / L, Al 0.067g / L, Si 0.05g / L, Fe 0.28g / L, Na+K 0.733g / L.

[0047] 3) Add the prepared 15% polyaluminium chloride to the desiliconized solution to remove iron, the molar ratio of the added amount to the iron in the desiliconized solution is 4:1, the deironization reaction pH is 7, the deironization temperature is 80°C, the reaction time is 0.5h, and the deironized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.017g / L, Al 0.007g / L, Si 0.05g / L, Fe 0.08g / L, Na+K 0.733g / L. Add 2mL of 1g / L sodium carboxymethyl starch solution to the deironized solution for flocculation and sedimentation to remove impurities. Flocculation for 2min can obtain a clear solution. After filtration, a clear flocculated solution is obtained. The impurity ion concentrations in the solution are: Ca 0.017g / L, Al 0.007g / L, Si 0.03g / L, Fe 0.08g / L, Na+K 0.333g / L.

[0048] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8, the amount of ammonium metavanadate seed added is 1 g / L, the crystallization end temperature is 30°C, the crystallization time is 4 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.01 g / L, Al 0.057 g / L, Si 0.02 g / L, Fe 0.05 g / L, Na+K 0.3 g / L.

[0049] The purity of the high-purity ammonium metavanadate finally produced is greater than 99.5%, and the impurity contents are: Ca 0.032%, Al 0.034%, Si 0.083%, Fe 0.062%, and Na+K 0.19%.

[0050] Example 2

[0051] Ammonium polyvanadate with a V2O5 content of 85% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.3%, Al 0.3%, Si 0.4%, Fe 0.5%, and Na+K 2%.

[0052] 1) Mix ammonium polyvanadate and solution at a ratio of 17:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.18g / L, Al 0.18g / L, Si 0.26g / L, Fe 0.29g / L, Na+K1.18g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 9, and the ammonium transfer reaction time is 1h;

[0053] 2) Add 15% calcium oxide to remove silicon, the molar ratio of the added amount to the silicon in the ammonium conversion solution is 4:1, the desiliconization pH is 8.5, the desiliconization temperature is 80°C, the reaction time is 1h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.09g / L, Al 0.09g / L, Si 0.05g / L, Fe 0.26g / L, Na+K 1.15g / L.

[0054] 3) Add the prepared 15% polyaluminium sulfate to the desiliconized solution to remove iron, the molar ratio of the added amount to the iron in the desiliconized solution is 6:1, the deironization reaction pH is 7.6, the deironization temperature is 90°C, the reaction time is 1h, and the deironized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.03g / L, Al 0.06g / L, Si0.04g / L, Fe 0.07g / L, Na+K 1.08g / L. Add 5mL of 2g / L sodium carboxymethyl starch solution to the deironized solution for flocculation and sedimentation to remove impurities. Flocculation for 2min can obtain a clear solution. After filtration, a clear flocculated solution is obtained. The impurity ion concentrations in the solution are: Ca 0.02g / L, Al 0.05g / L, Si0.03g / L, Fe 0.07g / L, Na+K 1.06g / L.

[0055] 4) Cooling and crystallizing the de-iron flocculated liquid, the crystallization pH is 9, the amount of ammonium metavanadate seed added is 1.5 g / L, the crystallization end temperature is 50°C, the crystallization time is 6 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.01 g / L, Al 0.05 g / L, Si 0.02 g / L, Fe 0.04 g / L, Na+K 0.82 g / L.

[0056] The high-purity ammonium metavanadate finally produced has a purity greater than 99.8%, and the impurity contents are: Ca 0.032%, Al 0.028%, Si 0.046%, Fe 0.061%, and Na+K 0.11%.

[0057] Example 3

[0058] Ammonium polyvanadate with a V2O5 content of 89% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.12%, Al 0.13%, Si 0.35%, Fe 0.38%, and Na+K 1.7%.

[0059] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.08g / L, Al 0.087g / L, Si 0.233g / L, Fe 0.2g / L, Na+K 1.133g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 8, and the ammonium transfer reaction time is 0.8h;

[0060] 2) Add 12% polyferric sulfate to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 3:1, the desiliconization pH is 8.3, the desiliconization temperature is 75°C, the reaction time is 0.7h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.03g / L, Al 0.087g / L, Si 0.12g / L, Fe 0.18g / L, Na+K 0.993g / L. The prepared 17% polyaluminium chloride was added to the desiliconized liquid to remove iron. The molar ratio of the added amount to the iron in the desiliconized solution was 5:1. The deironization reaction pH was 7.5, the deironization temperature was 88°C, the reaction time was 0.6h, and the deironized liquid was obtained after filtration. The impurity ion concentrations in the solution were: Ca 0.017g / L, Al 0.03g / L, Si 0.11g / L, Fe 0.09g / L, Na+K 0.83g / L.

[0061] 3) Add 3 mL of sodium carboxymethyl starch solution with a concentration of 1.6 g / L to the iron-removed liquid for flocculation and sedimentation to remove impurities. A clear solution can be obtained by flocculation for 2 minutes. After filtration, a clear flocculated liquid is obtained. The impurity ion concentrations in the solution are: Ca 0.017 g / L, Al 0.01 g / L, Si 0.05 g / L, Fe 0.08 g / L, and Na+K 0.35 g / L.

[0062] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8.8, the amount of ammonium metavanadate seed added is 1.4 g / L, the crystallization end temperature is 40°C, the crystallization time is 5 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.012 g / L, Al 0.007 g / L, Si 0.02 g / L, Fe 0.05 g / L, Na+K 0.3 g / L.

[0063] The high-purity ammonium metavanadate finally produced has a purity greater than 99.6%, and the impurity contents are: Ca 0.031%, Al 0.031%, Si 0.073%, Fe 0.064%, and Na+K 0.18%.

[0064] Example 4

[0065] Ammonium polyvanadate with a V2O5 content of 88% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.11%, Al 0.13%, Si 0.3%, Fe 0.33%, and Na+K 1.5%.

[0066] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.073g / L, Al 0.087g / L, Si 0.20g / L, Fe 0.22g / L, Na+K 1.0g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 8.6, and the ammonium transfer reaction time is 0.8h;

[0067] 2) Add 13% polyferric sulfate to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 3.5:1, the desiliconization pH is 8.4, the desiliconization temperature is 78°C, the reaction time is 0.8h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.07g / L, Al 0.09g / L, Si 0.05g / L, Fe 0.32g / L, Na+K 0.93g / L. The prepared 16% polyaluminium sulfate was added to the desiliconized liquid to remove iron. The molar ratio of the added amount to the iron in the desiliconized solution was 4.5:1. The deironization reaction pH was 7.4, the deironization temperature was 85°C, the reaction time was 0.9h, and the deironized liquid was obtained after filtration. The impurity ion concentrations in the solution were: Ca 0.04g / L, Al 0.05g / L, Si 0.05g / L, Fe 0.09g / L, Na+K 0.9g / L.

[0068] 3) Add 3.5 mL of 1.8 g / L sodium carboxymethyl starch solution to the deironed liquid for flocculation and sedimentation to remove impurities. A clear solution can be obtained by flocculation for 2 minutes. After filtration, a clear flocculated liquid is obtained. The impurity ion concentrations in the solution are: Ca 0.017 g / L, Al 0.01 g / L, Si 0.03 g / L, Fe 0.08 g / L, and Na+K 0.36 g / L.

[0069] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8.4, the amount of ammonium metavanadate seed added is 1.4 g / L, the crystallization end temperature is 35°C, the crystallization time is 5.5 h, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.012 g / L, Al 0.01 g / L, Si 0.02 g / L, Fe 0.05 g / L, Na+K 0.32 g / L.

[0070] The high-purity ammonium metavanadate finally produced has a purity greater than 99.7%, and the impurity contents are: Ca 0.042%, Al 0.034%, Si 0.081%, Fe 0.056%, and Na+K 0.15%.

[0071] Example 5

[0072] Ammonium polyvanadate with a V2O5 content of 87% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.22%, Al 0.21%, Si 0.29%, Fe 0.38%, and Na+K 1.6%.

[0073] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.147g / L, Al 0.14g / L, Si 0.193g / L, Fe 0.253g / L, Na+K 1.067g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 7.8, and the ammonium transfer reaction time is 0.9h;

[0074] 2) Add 14% polyferric sulfate to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 2.8:1, the desiliconization pH is 8.3, the desiliconization temperature is 73°C, the reaction time is 0.9h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.02g / L, Al 0.1g / L, Si 0.03g / L, Fe 0.3g / L, Na+K 1.53g / L. The prepared 15% polyaluminium chloride was added to the desiliconized liquid to remove iron. The molar ratio of the added amount to the iron in the desiliconized solution was 4:1. The pH of the deironization reaction was 7.3, the deironization temperature was 88°C, the reaction time was 0.5h, and the deironized liquid was obtained after filtration. The impurity ion concentrations in the solution were: Ca 0.017g / L, Al 0.007g / L, Si 0.03g / L, Fe 0.1g / L, Na+K 1.46g / L.

[0075] 3) Add 4 mL of 1 g / L sodium carboxymethyl starch solution to the deironed liquid for flocculation and sedimentation to remove impurities. A clear solution can be obtained by flocculation for 2 minutes. After filtration, a clear flocculated liquid is obtained. The impurity ion concentrations in the solution are: Ca 0.017 g / L, Al 0.007 g / L, Si 0.02 g / L, Fe 0.08 g / L, and Na+K 0.52 g / L.

[0076] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8.5, the amount of ammonium metavanadate seed added is 1.4 g / L, the crystallization end temperature is 30°C, the crystallization time is 6 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.013 g / L, Al 0.005 g / L, Si 0.02 g / L, Fe 0.05 g / L, Na+K 0.42 g / L.

[0077] The purity of the high-purity ammonium metavanadate finally produced is greater than 99.6%, and the impurity contents are: Ca 0.033%, Al 0.039%, Si 0.081%, Fe 0.064%, Na+K 0.14%.

[0078] Example 6

[0079] Ammonium polyvanadate with a V2O5 content of 88.5% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.13%, Al 0.15%, Si 0.33%, Fe 0.34%, and Na+K 1.2%.

[0080] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.087g / L, Al 0.1g / L, Si 0.22g / L, Fe 0.227g / L, Na+K 0.8g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 7.5, and the ammonium transfer reaction time is 0.5h;

[0081] 2) Add 12% calcium oxide to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 4:1, the pH of silicon removal is 8.3, the temperature of silicon removal is 75℃, the reaction time is 0.5h, and the desiliconized liquid is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.012g / L, Al 0.067g / L, Si 0.1g / L, Fe 0.22g / L, Na+K 0.73g / L. Add 13% polyaluminium chloride to the desiliconized liquid to remove iron, the molar ratio of the amount added to the iron in the desiliconized solution is 4:1, the pH of the deferrification reaction is 7, the temperature of the deferrification is 90℃, the reaction time is 0.5h, and the deferrified liquid is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.011g / L, Al 0.04g / L, Si 0.08g / L, Fe 0.08g / L, Na+K 0.7g / L.

[0082] 3) Add 2 mL of 1.6 g / L sodium carboxymethyl starch solution to the deironed liquid for flocculation and sedimentation to remove impurities. A clear solution can be obtained by flocculation for 2 minutes. After filtration, a clear flocculated liquid is obtained. The impurity ion concentrations in the solution are: Ca 0.01 g / L, Al 0.008 g / L, Si 0.03 g / L, Fe 0.08 g / L, and Na+K 0.44 g / L.

[0083] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8.6, the amount of ammonium metavanadate seed added is 1 g / L, the crystallization end temperature is 40°C, the crystallization time is 4 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.01 g / L, Al 0.007 g / L, Si 0.02 g / L, Fe 0.06 g / L, Na+K 0.38 g / L.

[0084] The high-purity ammonium metavanadate finally produced has a purity greater than 99.5%, and the impurity contents are: Ca 0.032%, Al 0.031%, Si 0.062%, Fe 0.061%, and Na+K 0.2%.

[0085] Example 7

[0086] Ammonium polyvanadate with a V2O5 content of 86.9% was selected as the purification raw material, and the impurity contents in the raw material were: Ca 0.13%, Al 0.1%, Si 0.25%, Fe 0.34%, and Na+K 1.4%.

[0087] 1) Mix ammonium polyvanadate and solution at a ratio of 15:1 to dissolve to obtain ammonium metavanadate solution, the impurity ion content of the solution is: Ca 0.087g / L, Al 0.067g / L, Si 0.167g / L, Fe 0.227g / L, Na+K 0.933g / L, and heat to perform ammonium transfer reaction. Add ammonia water to adjust the solution pH to 8.2, and the ammonium transfer reaction time is 0.5h;

[0088] 2) Add 10% polyferric sulfate to remove silicon, the molar ratio of the amount added to the silicon in the ammonium conversion solution is 3:1, the desiliconization pH is 8, the desiliconization temperature is 79°C, the reaction time is 0.5h, and the desiliconized solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.017g / L, Al 0.067g / L, Si 0.07g / L, Fe 0.23g / L, Na+K 0.83g / L.

[0089] 3) Add the prepared 15% polyaluminium chloride to the desiliconized solution to remove iron, the molar ratio of the added amount to the iron in the desiliconized solution is 4:1, the deferrification reaction pH is 7, the deferrification temperature is 88°C, the reaction time is 0.5h, and the deferrified solution is obtained after filtration. The impurity ion concentrations in the solution are: Ca 0.015g / L, Al 0.007g / L, Si 0.07g / L, Fe 0.09g / L, Na+K 0.733g / L. Add 5mL of 1g / L sodium carboxymethyl starch solution to the deferrified solution for flocculation and sedimentation to remove impurities. Flocculation for 2min can obtain a clear solution. After filtration, a clear flocculated solution is obtained. The impurity ion concentrations in the solution are: Ca 0.013g / L, Al 0.007g / L, Si 0.03g / L, Fe 0.08g / L, Na+K 0.23g / L.

[0090] 4) Cooling and crystallizing the flocculated solution after iron removal, the crystallization pH is 8.6, the amount of ammonium metavanadate seed added is 1 g / L, the crystallization end temperature is 45°C, the crystallization time is 4 hours, and the slurry after crystallization is filtered to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity ion concentrations in the crystallization mother liquor are: Ca 0.01 g / L, Al 0.007 g / L, Si 0.02 g / L, Fe 0.06 g / L, Na+K 0.21 g / L.

[0091] The high-purity ammonium metavanadate finally produced has a purity greater than 99.8%, and the impurity contents are: Ca 0.023%, Al 0.033%, Si 0.084%, Fe 0.042%, and Na+K 0.2%.

[0092] Comparative Example 1

[0093] For comparison of purification effects, when the solution pH was adjusted to 8.5, polyferric sulfate was added to remove silicon, and polyaluminium chloride was not added to remove iron. The other conditions were the same as those in Example 3.

[0094] The high-purity ammonium metavanadate finally produced has a purity of 98.5%, and the impurity contents are: Ca 0.034%, Al 0.034%, Si 0.075%, Fe 0.295%, and Na+K 0.18%.

[0095] Comparative Example 2

[0096] For comparison of purification effects, when the solution pH was adjusted to 7.5, polyaluminium chloride was added to remove iron, and polyferric sulfate was not added to remove silicon. The other conditions were the same as in Example 5.

[0097] The high-purity ammonium metavanadate finally produced has a purity of 98.9%, and the impurity contents are: Ca 0.033%, Al 0.038%, Si 0.152%, Fe 0.061%, and Na+K 0.14%.

[0098] Comparative Example 3

[0099] To compare the purification effects, the solution pH was first adjusted to 7.5 and polyaluminium chloride was added to remove iron, and then the solution pH was adjusted to 8.3 and polyferric sulfate was added to remove silicon. The other conditions were the same as in Example 3.

[0100] The high-purity ammonium metavanadate finally produced has a purity of 98.0%, and the impurity contents are: Ca 0.031%, Al 0.092%, Si 0.335%, Fe 0.364%, and Na+K 0.9%.

[0101] The purity of the ammonium metavanadate prepared by purification in the above examples and comparative examples and the content of related impurities are summarized in Table 1.

[0102] Table 1:

[0103]

[0104] It is not difficult to see from Table 1 that the ammonium metavanadate obtained in Examples 1-7 has a low impurity content and a purity higher than 99.5%, which meets the purity requirements of vanadium products used in electrolytes and aviation manufacturing. By comparing the examples, it is found that adding different silicon removal agents or iron removal agents is particularly important for the preparation of high-purity ammonium metavanadate, and at the same time, a suitable solution pH value and silicon removal or iron removal sequence are selected, otherwise the product purity will not meet the standard.

[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for purifying ammonium polyvanadate to prepare high-purity ammonium metavanadate, characterized in that the steps include: S1. After dissolving the ammonium polyvanadate, adding ammonia water to carry out the ammonium conversion reaction; S2. The pH value of the solution after ammonium conversion is adjusted to 8-8.5, and then a desiliconizing agent is added, and the solution is filtered after sufficient desiliconization; S3. The pH value of the solution obtained in step S2 was adjusted to 7-7.6, and then an iron removal agent and sodium carboxymethyl starch solution were added, and the mixture was fully flocculated and filtered; S4. The pH value of the solution obtained in step S2 is adjusted to 8-9, then cooled and crystallized, and filtered to obtain high-purity ammonium metavanadate; The silicon removal agent is polyferric sulfate and / or calcium oxide; The iron removal agent is polyaluminium chloride and / or polyaluminium sulfate.

2. The method according to claim 1, characterized in that The content of V2O5 in the ammonium polyvanadate is 85-90%, and the impurities include: Ca 0.1-0.3%, Al 0.1-0.3%, Si 0.25-0.4%, Fe 0.3-0.5%, and the sum of Na and K is 1.1-2.0%.

3. The method according to claim 1, characterized in that In step S1, during the transammonium reaction, ammonia water is added to a pH of 7-9, and the transammonium reaction time is 0.5-1h.

4. The method according to claim 1, characterized in that: In step S2, the concentration of the desiliconizing agent is 10-15wt%; the molar ratio of the amount of the desiliconizing agent added to the silicon in the solution after the ammonium conversion is (2-4):

1.

5. The method according to claim 1, characterized in that In step S2, the desiliconization reaction temperature is 70-80°C, and the reaction time is 0.5-1h.

6. The method according to claim 1, characterized in that In step S3, the concentration of the deironing agent is 15-20wt%; the molar ratio of the amount of the deironing agent added to the iron in the desiliconizing liquid is (4-6):

1.

7. The method according to claim 1, characterized in that In step S3, the iron removal reaction temperature is 80-90° C. and the reaction time is 0.5-1 h.

8. The method according to claim 1, characterized in that: In step S3, the concentration of the sodium carboxymethyl starch is 1-2 g / L, and the added amount is 2-5 mL / L.

9. The method according to claim 1, characterized in that: In step S4, seed crystals are added during the crystallization of ammonium metavanadate in an amount of 1-1.5 g / L, the crystallization endpoint temperature is 30-50° C., and the crystallization time is 4-6 h.

10. The method according to claim 1, characterized in that In step S4, the filtered mother liquor is used to dissolve ammonium polyvanadate in step S1.

Citation Information

Patent Citations

  • Ammonium metavanadate and preparation method thereof

    CN107285381A

  • Purification method of ammonium metavanadate and high-purity ammonium metavanadate

    CN107298461A